A case report of extranodal NK/T-cell lymphoma in patient with chronic lymphocytic leukemia. Issue 30 (July 2018) - Ge, Hangping; Wu, Xiangping; Shen, Jianping; Chen, Junfa; Chen, Ying; Zhang, Yu
Abstract: Rationale: Chronic lymphocytic leukemia often results in secondary tumors, the most common being large B cell lymphoma known as Richter syndrome, followed by extranodal NK/T-cell lymphoma (nasal type) is extremely rare. Patient concerns: A chronic lymphocytic leukemia patient presented with nasal congestion. Diagnoses: Nasal endoscopy identified a left nasal mass, and the pathology suggested extranodal NK/T-cell lymphoma (nasal type). Interventions: The patient received a course of chemotherapy. Outcomes: Pneumonia and coagulopathy occurred after chemotherapy, and the patient died shortly thereafter. Lessons: It is essential to recognize the transformation of disease earlier in chronic lymphoblastic leukemia patient.